Ketogenic diet treatment for super-refractory status epilepticus in the intensive care unit: feasibility, safety and effectiveness - Yishu Ren; Mengyao Zhang; Xinxiao Fu; Yan Zhang; Fang Liu; Chenglin Wu; Haiyan Shi; Fei Tian; Gang Liu; Yicong Lin; Yingying Su; Weibi Chen (Frontiers in Neurology)
Background and aimsTo investigate the feasibility, safety and effectiveness of the ketogenic diet (KD) for super-refractory status epilepticus (SRSE) in the intensive care unit (ICU).MethodsWe conducted a prospective investigation on patients with SRSE treated with the KD. The primary outcome measures were ketosis development as a biomarker of feasibility and resolution of SRSE as effectiveness. KD-related side effects were also investigated.ResultsTwelve patients (9 females and 3 males) with SRSE, with a median age of 34 years [range 16–69, interquartile range (IQR) 18–52], were treated with a KD. The median duration of SRSE prior to KD treatment was 21 days (range 4–46). SRSE resolved in 75% (9/12) of patients at a median of 3 days (range 1–18) after KD initiation. Among the nine KD responders, all were successfully weaned off anesthetic agents at a median of 16 days (range 4–32) after KD initiation, and all were also successfully weaned off ventilator. Side effects varied, and included gastrointestinal intolerances, malnutrition and metabolic abnormalities, electrolyte disturbance, and acute weight loss, although most of them could be corrected. No patient died due to KD, and neurofunctions continued to improve under KD therapy.ConclusionThe KD may be feasible and effective for the treatment of SRSE in the ICU. Moreover, it is relatively safe. However, there are numerous adverse events that can be corrected under close monitoring.